THE EDUCATIONAL REFORMS OF ALFRED THE GREAT - Eldorbek Erkin og’li Khamitov,; Jumaniyozova Xurshida Azimjon qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper explores the educational initiatives undertaken by Alfred the Great, King of Wessex (871–899), who is celebrated as one of early medieval England’s most impactful rulers. Alfred observed that low levels of literacy and learning among his people  threatened  both  effective  governance  and  the  preservation  of  Anglo-Saxon culture and Christian traditions. To address this, he implemented reforms designed to promote education, improve literacy, and make important knowledge more accessible by translating key Latin texts into Old English. The study emphasizes Alfred’s efforts to enhance literacy among clergy, nobles, and  even  common  citizens,  highlighting  the  connection  between  education,  moral development,  and  administrative  efficiency.  By  commissioning  translations  of religious works, historical accounts, and practical manuals, Alfred aimed to safeguard cultural heritage while stimulating intellectual growth. His policies also encouraged the establishment of schools and learning centers within monasteries, which served as focal points for education and scholarship.